Clinical Presentation and Nursing Management of Obturator Hernia-An Updated Review - Albalwi, Bader Musllm Musllm; Meaad Saleem Dohem Almutairy; Meead Othman Alshwaiman; Ibrahim Ali Abdullah Abu Habibah; Saleh Ali Bunimah; Rana Ibrahim Al Musabbihi; Mayadah Ali Alhazmi; Saleh Talea Sarar Alqahtani; Abdulla Ali Qubuli; Saad Mohamad Saad Alzaml; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Obturator hernia is a rare and frequently overlooked type of pelvic hernia, predominantly affecting elderly, underweight women. Its deep anatomical location and nonspecific clinical manifestations often result in delayed diagnosis, which contributes to high rates of bowel obstruction, strangulation, and mortality. Despite advances in imaging and surgical techniques, obturator hernia remains a diagnostic challenge in emergency and surgical practice. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review aims to summarize the current evidence on the clinical presentation, etiological factors, diagnostic strategies, and nursing and surgical management of obturator hernia, with emphasis on improving early recognition and patient outcomes. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> An updated narrative review of the literature was conducted focusing on anatomy, epidemiology, etiology, clinical features, diagnostic modalities, surgical management options, nursing care, and postoperative outcomes related to obturator hernia. Relevant peer-reviewed studies, clinical reports, and review articles were analyzed and synthesized. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Obturator hernia occurs most commonly in frail elderly women due to pelvic anatomical differences, loss of protective fat, and chronic increases in intra-abdominal pressure. Clinical presentation is often nonspecific and may include bowel obstruction, abdominal pain, or medial thigh pain caused by obturator nerve compression. Computed tomography of the abdomen and pelvis is the diagnostic modality of choice, offering high sensitivity. Definitive management is surgical, with laparoscopic and open approaches both demonstrating effectiveness. Early intervention significantly reduces morbidity and mortality. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Early clinical suspicion combined with timely imaging and prompt surgical management is crucial for improving outcomes in patients with obturator hernia.